PENCITRAAN ALIRAN FLUIDA 3 MEDIUM DENGAN TOMOGRAFI ULTRASONIK - Tatang Gunar Setiadji; Sutrisno Salomo Hutagalung (CommIT Journal, 2009)
In the imaging process, computer technology has a big role in reconstruction. This paper describes imaging the fluid flow imaging in three medium using ultrasonic tomography for reconstructing the cross sectional image. The image based on wave velocity in each medium and the time of flight are obtained from the measurements using transducer that placed around the pipe. Data collection is constructed into parallel form, then with the use of filtered back projection algorithm an image can be reconstructed. The resolution of image is limited by the number of data of each projection in order to obtain high accuracy of resolution. To increase image resolution, data is interpolated using computer with Matlab. Keywords: image reconstruction, three medium, ultrasonic tomography, filtered back projection